Amphiregulin (AREG) and Epiregulin (EREG) Gene Expression as Predictor for Overall Survival (OS) in Oxaliplatin/Fluoropyrimidine Plus Bevacizumab Treated mCRC Patients—Analysis of the Phase III AIO KRK-0207 Trial - Stintzing, Sebastian; Ivanova, Boryana; Ricard, Ingrid; Jung, Andreas; Kirchner, Thomas; Tannapfel, Andrea; Juette, Hendrik; Hegewisch-Becker, Susanna; Arnold, Dirk; Reinacher-Schick, Anke (Frontiers in Oncology, 2018)
Background The EGFR (epithelial growth factor receptor) ligands amphiregulin (AREG) and epiregulin (EREG) have been considered as predictors for EGFR-antibody efficacy. The effect of AREG and EREG expression levels in primary tumor samples on the outcome of bevacizumab-treated patients is unknown. Patients and Methods Formalin-fixed paraffin-embedded (FFPE) tumor samples from surgically removed primaries of the AIO KRK-0207 trial have been tested for AREG and EREG expression. The AIO KRK-0207 trial was a randomized phase-3 study to investigate the best maintenance strategy after oxaliplatin/fluoropyrimidine plus bevacizumab induction treatment in patients with mCRC. Association of AREG and EREG levels with outcome parameters were investigated, taking into account RAS and BRAF mutations. Results A total of 331 tumor samples had measurable AREG and EREG tissue levels. In the total cohort using continuous expression levels, higher logAREG and logEREG levels were asso-ciated with a significant longer overall survival (OS) (HR 0.80; p= 0.003 and HR 0.78; p= 0.001 respectively). The subgroup of BRAF mutant tumors displayed significantly lower AREG and EREG levels compared to wild-type tumors. The prognostic effect of AREG and EREG expression was limited to the double wild-type subpopulation, whereas in the RAS mutant and BRAF mutant subgroups no prognostic effect was detected. Conclusion Low logAREG and logEREG levels are associated with a shorter OS in oxali-platin/fluoropyrimidine plus bevacizumab treated patients. As low AREG and EREG level are associated with BRAF mutations, the prognostic value of EREG and AREG levels is limited to the RAS and BRAF wild-type subpopulation.